IMPORTANCE OF SOURCE CONTROL IN THE SUBGROUP OF INTRA-ABDOMINAL INFECTIONS FOR SEPTIC SHOCK PATIENTS: ANALYSIS OF 390 CASES - Uğur Önal; Deniz Akyol; Olcay Buse Kenanoğlu; Merve Mert; Dilşah Başkol; Seichan Chousein Memetali; Gamze Şanlıdağ; Cansu Bulut; Arda Kaya; Ayşe Uyan Önal; Nazlıhan Yalçın; Günel Guliyeva; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: In this study it was aimed to evaluate the efficacy and timing with technique of the source control for the subgroup of septic shock (SS) patients with intraabdominal infections (IAI) in a tertiary-care educational hospital.